Loneliness of the Blind and the Visually Impaired - Rokach, Ami; Berman, David; Rose, Alison (Frontiers in Psychology, 2021)
Loneliness has been termed a social epidemic, especially when experienced by people with disabilities. The present study compared the blind and visually impaired with the general population not on the frequency or intensity of their loneliness, but on its qualitative aspects. A 30-item yes/no questionnaire was utilized, and measured the qualitative aspects of loneliness on five subscales: Emotional distress, social inadequacy, Growth and discovery, Social isolation and emotional alienation. As expected, the two populations differed significantly in their scores on four of the five subscales (except emotional alienation), but in the opposite direction of which was expected. The article provides an explanation for these unexpected results.